Cerebral Blood Flow Hemispheric Asymmetry in Comatose Adults Receiving Extracorporeal Membrane Oxygenation - Johnson, Thomas W.; Dar, Irfaan A.; Donohue, Kelly L.; Xu, Yama Y.; Santiago, Esmeralda; Selioutski, Olga; Marinescu, Mark A.; Maddox, Ross K.; Wu, Tong Tong; Schifitto, Giovanni; Gosev, Igor; Choe, Regine; et al. (Frontiers in Neuroscience, 2022)
Peripheral veno-arterial extracorporeal membrane oxygenation (ECMO) artificially oxygenates and circulates blood retrograde from the femoral artery, potentially exposing the brain to asymmetric perfusion. Though ECMO patients frequently experience brain injury, neurologic exams and imaging are difficult to obtain. Diffuse correlation spectroscopy (DCS) non-invasively measures relative cerebral blood flow (rBF) at the bedside using an optical probe on each side of the forehead. In this study we observed interhemispheric rBF differences in response to mean arterial pressure (MAP) changes in adult ECMO recipients. We recruited 13 subjects aged 21-78 years (7 with cardiac arrest, 4 with acute heart failure, and 2 with acute respiratory distress syndrome). They were dichotomized via Glasgow Coma Scale Motor score (GCS-M) into comatose (GCS-M≤4; n=4) and non-comatose (GCS M>4; n=9) groups. Comatose patients had greater interhemispheric rBF asymmetry (ASYMrBF) vs. non-comatose patients over a range of MAP values (29% vs. 11%, p=0.009). ASYMrBF in comatose patients resolved near a MAP range of 70-80 mmHg, while rBF remained symmetric through a wider MAP range in non-comatose patients. Correlations between post-oxygenator pCO2 or pH vs. ASYMrBF were significantly different between comatose and non-comatose groups. Our findings indicate that comatose patients are more likely to have asymmetric cerebral perfusion.